(untitled) (Public Sector Economics - submission site, 2023)
The use of formal and informal care for the elderly depends on many factors: income, urban-rural environment, educational attainment, family composition (singles/multi-member family), age and severity of health complications. For this analysis, a pro-rich poverty model is used based on data from the latest (8th) edition of SHARE (Survey of Health, Aging and Retirement in Europe) to examine the impact of socioeconomic inequalities among older people in the use of home care in European Union. The main results indicate that the pro-poor distribution of long-term care prevails in most of the studied countries. At the same time, health variables contribute to pro-poor inequality in the use of long-term care, mainly in informal care. When it comes to formal care, most countries have pro-poor contributions. Formal care inequalities disappeared when adjusted for need factors, while informal care inequalities remained in most countries.